2000
DOI: 10.1034/j.1600-051x.2000.027006417.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial comparison of smoker and non‐smoker adult and early‐onset periodontitis patients by polymerase chain reaction

Abstract: A number of bacterial species are involved in the aetiology of periodontitis and include Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, Bacteroides forsythus and Treponema denticola. Several studies have shown differences in the microflora between the various forms of periodontal disease. It is recognised that smoking is a risk factor for periodontal disease, but there are conflicting reports on whether or not smoking has an effect on the periodontal microflora. We utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
108
4
11

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(148 citation statements)
references
References 49 publications
25
108
4
11
Order By: Relevance
“…Thus, it appears that tobacco smoking is associated with a reduced inflammatory response in terms of gingival bleeding. This finding is in agreement with those of numerous epidemiological and clinical studies reported previously with regard to cigarette smoking (Bergström & Flodérus-Myrhed 1983, Preber & Bergström 1985, Bergström 1990, Danielsen et al 1990, Lie et al 1998, Darby et al 2000, Dietrich et al 2004). …”
Section: Gingival Healthsupporting
confidence: 83%
“…Thus, it appears that tobacco smoking is associated with a reduced inflammatory response in terms of gingival bleeding. This finding is in agreement with those of numerous epidemiological and clinical studies reported previously with regard to cigarette smoking (Bergström & Flodérus-Myrhed 1983, Preber & Bergström 1985, Bergström 1990, Danielsen et al 1990, Lie et al 1998, Darby et al 2000, Dietrich et al 2004). …”
Section: Gingival Healthsupporting
confidence: 83%
“…27 Microbiological studies showed that smokers had a higher prevalence of bacterial species related to periodontal disease compared to nonsmokers, including Porphyromonas gingivalis, Aggregatibacter actinomycetencomitans, Bacteroides forsythus, 28 Prevotella intermedia, Fusobacterium nucleatum. However, some authors reported no differences between smokers and nonsmokers with respect to the detection of periodontal pathogens, 29,30 both in terms of prevalence 31 and amount of bacteria 32 in the subgingival microbiota. Recent studies, using real time PCR, have demonstrated a positive relationship between degree of smoking and amount of bacteria/probing depth.…”
Section: Biological Effects and Eventsmentioning
confidence: 99%
“…On the other hand, Bouloukaki et al 62 suggested that, there is an increase of CD8 + T-cells and a decrease of the CD4 + /CD8 + within 6 months after smoking cessation. Morozumi et al 46 state that it takes more than 8 weeks for levels of IL-1β, IL-8, TNF-α and VEGF Braz Oral Res., (São Paulo) 2012;26(Spec Iss 1): [25][26][27][28][29][30][31] to return to their normal values, and that the role (or function) of neutrophils is still not completely recovered after this period.…”
Section: Smoking Cessation and Periodontal Tissuesmentioning
confidence: 99%
“…Whether due to limitations in the microbiological techniques used or simply to our inability to clinically distinguish certain cases of AgP from CP, no differences in subgingival microbial detection emerged in several studies. 35,37,38,40 We recently reported results of a study on polymerase chain reaction (PCR) detection of A. actinomycetemcomitans or P. gingivalis from subgingival plaque samples of 267 periodontitis patients (84 diagnosed with AgP and 183 with CP). 30 In this patient sample, CP cases had higher detection of both bacteria compared with AgP, although the differences were not statistically significant.…”
mentioning
confidence: 99%